HUBUNGAN PENGGUNAAN MEDIA INTERNET DENGAN HASIL BELAJAR DESAIN BUSANA PESTA SISWA SEKOLAH MENENGAH KEJURUAN: Media internet, hasil belajar desain busana pesta - Ariani, Meylisa; Desy Tri Inayah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2024)
The purpose of this study was to determine: (1) the relationship between the use of internet media and the learning outcomes of party dress design, (2) the categoriesof internet media use in learning party dress design, and (3) the categories of learning outcomes of party dress design. This research includes the type of ex-postfacto research. The population in this study was all 102 class XI students. The sample was 70 students using purposive sampling. Methods of data collection usedquestionnaires and documentation. Instrument testing was carried out on 32 students. The validity test results obtained that 4 items were declared invalid and the value of rii = 0.936. Data analysis techniques used descriptive analysis techniques and product-moment correlation tests. The results showed that (1) there was a positive and significant relationship between the use of internet mediaand the learning outcomes of fashion design for class XI with a value of r count = 0.646 > rtable = 0.277; (2) most of the use of internet media in learning fashion design is in the medium category; (3) the most of the learning outcomes of fashion design are classified as very high